Karakteristik dan Komposisi Asam Lemak pada Minyak Biji Kenaf dari Lima Varietas Karangploso (KR) (Hibiscus cannabinus L.) - Elda Nurnasari; Nurindah Nurindah (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
The Kenaf seed has narrow applications despite the relatively high oil content. This study therefore aims to identify the fatty acid content and chemical characteristics of kenaf seed oil derived from five superior varieties released by Balittas. These include Karangploso (KR) 6, 9, 11, 12, and 14, estimated to have oil content between the range 22.71–32.-32%. Furthermore, the quality is determined by testing several parameters, encompassing the acid number, free fatty acid level, iodine, saponification and peroxide number. The result show an acid rate range of 2.21 mg KOH/g (KR 12) - 3.28 mg KOH/g (KR 11) in kenaf seed oil. Meanwhile, the free fatty acids varied from 1.10–1.64%, with saponification (194.97–243.91 mg KOH/g) iodine rate (54.72– 71.44 g Iod/100 g) and peroxide rate (33.97 mec/kg (KR 14) - 56.23 mec/kg (KR 6)). The kenaf seed oil was concluded to contain numerous essential fatty acids, and oleic acid (44.73% KR 9; 43.01% KR 14), as well as linoleic acid (42.19% KR 12) exhibited the highest amounts.